Impact Investment in Agriculture in Africa: A Case study of Ethiopia, Sudan, Mali, and Senegal - Agyekumhene, Christopher; Derenoncourt, Marie Ena; Tetteh-Addo, Philemon; Wathuta, William; Newman, Richard; Grosjean, Godefroy; Costa, Ciniro (2022)
Climate change is a growing threat to agricultural production in sub-Saharan Africa, leading to rising poverty and malnutrition. Implementing climate smart agricultural practices at scale will require substantial investments from private and public actors. To understand the impacts of recent investments, challenges and perspectives, this study analyzes agricultural value chain investments in four African countries in the Sahel region: Senegal, Mali, Ethiopia, and Sudan. The study identifies priority value chains with potential for CSA investment and characterizes key investment opportunities within these value chains that could be attractive for investors given the country context. Yet, the pathway from potential to actual CSA investment remains fraught with challenges that will require strategic and deliberate measures to counter. The use of grants and concessions through blended finance structures are critical to unlock inclusive and impactful investments. Investment facilitation programs and pipeline development can also contribute to scaling CSA investments in the region.